A Phenomenological Study of Lecturers’ Experience in Designing Curriculum in the Industry 4.0 Era - Moch. Bakhtiar; Nur Laila Rahmawati (Attanwir : Jurnal Keislaman dan Pendidikan, 2025)
Universities are at the forefront of preparing competent human resources to face the Industry 4.0 era, which is fraught with digital and technological disruption. Academic anxiety arises from the gap between the dynamic demands of the industry and the readiness of higher education institutions. This study aims to deeply explore and understand the meaning of the lived experiences of lecturers in the curriculum planning process in the Industry 4.0 era. Using a qualitative approach and a phenomenological method, this research seeks to uncover the essence of academics' challenges, hopes, and perceptions through in-depth interviews. The results identified three main themes from the lecturers' experiences: (1) Navigating the Tension between Academic Tradition and Industrial Disruption; (2) Efforts to Build Collaborative Bridges with external parties; and (3) Aspirations Towards an Adaptive Academic Ecosystem. This study concludes that understanding the essence of curriculum designers' experiences is key to creating more humane and relevant educational innovations amid changing times.